Learning lessons from China’s forest rehabilitation efforts: national level review and special focus on Guangdong Province - Chokkalingam, U.; Zhou Zaichi; Wang Chunfeng; Toma, T. (Center for International Forestry Research, 2006)
Rehabilitation of degraded forest lands has been ongoing in China for centuries. Efforts intensified from the 1980s as forest resources became scarcer and environmental problems worsened. This report presents the main results of a study assessing past and ongoing rehabilitation efforts through a national-level review and more detailed analysis for one province, Guangdong. In Guangdong, a provincial-level review was followed by an analysis of 22 cases and a multi-stakeholder consultative workshop. The initiatives ranged from large national and provincial government projects to state forest farm efforts, city landscape projects, private sector and joint initiatives. They differed in objectives, costs, implementation strategies, institutional arrangements and incentives offered to local people. The whole country, including Guangdong province has witnessed increased forest cover since the 1980s. But many rehabilitation sites have poor growth and stocking; and are highly susceptible to pests, diseases and fire. Both positive and negative environmental and socio-economic outcomes have been reported but systematic monitoring and evaluation has been limited. The private sector including household forest farms benefited from timber production where restraints such as high taxes and fees and harvesting quotas were absent or removed. Elsewhere, they found it easier to benefit from fruits and other non-timber products. In ecological forest sites, government compensation payments were far below the opportunity costs for use of the resources. Many large government projects could not maintain the rehabilitated areas in the long-term given a lack of sustained funding, active local participation and ownership. Locally-driven initiatives sensitive to local needs, site and market conditions tend to be more viable. Adequate benefit flow to local people, secure tenure rights over resources, and mutually-beneficial partnerships and institutional arrangements also help sustainability of the efforts. The report provides key recommendations for the relevant stakeholders to support, plan, implement and sustain forest rehabilitation in Guangdong and China overall.